The Influence of Using Animated Learning Media on Students Activities in Natural Science Course - Puspita, Tita; Sesrita, Afridha (Islamic Journal of Integrated Science Education (IJISE), 2022)
The purpose of this study was to determine the effect of using animation learning media on students’ activities in science subjects. The method used in this study was to use an experimental design using Posttest Only Control as a measuring tool and collected using a questionnaire technique used to determine the effect of using animation media on student activity in science lessons with a total of 20 students in the experimental class and 20 students in the control class so that the total number of respondents was 40 students. From the results of this research data analysis, it is known that posttest of the use of animation learning media in science lessons, the experimental and control classes have a sign value > 0.05, in the experimental class itself the significance value is 0.200 > 0.05, meaning that the significance value is greater than the significance value minimal. While in the control class itself, the significance value is 0.71 > 0.005, which is greater than the minimum limit. Based on the homogeneity and variance table data for the experimental class and the control class, the calculated significance for student activity in science subjects is 0.768. This means that the significance is greater than the minimum significance of 0.768 > 0.05, so it can be concluded that the variance of scores of the experimental and control groups is homogeneous.